2004
DOI: 10.1021/cm0353660
|View full text |Cite
|
Sign up to set email alerts
|

XRD and HREM Studies of Epitaxially Stabilized Hexagonal Orthoferrites RFeO3 (R = Eu−Lu)

Abstract: The formation of previously unknown hexagonal modifications of orthoferrites RFeO3 (R = Eu−Lu) was observed on ZrO2(Y2O3) (111) substrates at 900 °C. XRD and HREM studies reveal epitaxial growth of the hexagonal film. The structure of the hexagonal RFeO3 was assigned to the ferroelectric space group P63 cm. The typical structural defects in the hexagonal RMnO3 films on ZrO2(Y2O3) (111) are described. Parallel deposition on perovskite substrates results in the stable perovskite phase. The epitaxial stabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
91
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 17 publications
8
91
0
Order By: Relevance
“…Here it is found that the oxygen position parameters do not significantly vary with pressure. Moreover, for the general hexagonal (P6 3 cm) ABO 3 (A = RE, B= Mn, Fe and Ga) system, replacement of the A and/or B site by ions of different radii does not significantly modify the atomic positions [8,29,30,31]. Mn is approximately in the centre of its oxygen environment [32].…”
Section: Resultsmentioning
confidence: 96%
“…Here it is found that the oxygen position parameters do not significantly vary with pressure. Moreover, for the general hexagonal (P6 3 cm) ABO 3 (A = RE, B= Mn, Fe and Ga) system, replacement of the A and/or B site by ions of different radii does not significantly modify the atomic positions [8,29,30,31]. Mn is approximately in the centre of its oxygen environment [32].…”
Section: Resultsmentioning
confidence: 96%
“…1a) [11][12][13]17 . Recently, thin films of RFeO 3 rare-earth ferrites have been epitaxially stabilized in the hexa manganite P6 3 cm structure [20][21][22] . This new family of hexa materials exhibit ferroelectricity above room temperature, but with conflicting results as to its origin 23,24 .…”
mentioning
confidence: 99%
“…Using epitaxial stabilization, however, it is possible to make a metastable hexagonal polymorph of LuFeO 3 that is isostructural with YMnO 3 and other hexagonal rare-earth manganites. 21 In this hexagonal structure, LuFeO 3 has been measured to be both ferroelectric 22,23 and weakly ferromagnetic, [22][23][24] with first principles calculations predicting the ability to reverse the magnetization with a change in polarization. 25 It was recently reported that h-LuFeO 3 is antiferromagnetically ordered at room temperature with a canted antiferromagnetic ordering at T N = 130 K, 23 making it one of the few known room-temperature multiferroics (in this work we will refer to the onset of canted antiferromagnetic order, which is what we can measure, as the Néel temperature).…”
mentioning
confidence: 99%